Modified coal gasification fine slag composite material and preparation method and application thereof, phase change composite material and preparation method thereof
Patent Information
- Application Number
- CN202611039076.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-13
AI Technical Summary
但十四醇仍存在固-液相变材料的固有缺陷:一是固液相变过程中易流动泄漏,导致材料储热能力持续衰减、循环使用效率大幅降低;二是本征导热系数低,储放热响应速率慢、热滞后性显著,严重制约了储热系统的运行效率与温控精度,无法直接满足工程化应用要求,需依赖载体材料通过物理吸附、孔隙约束实现 “形状稳定化”
[0015]在本发明中,利用含氨基硅烷偶联剂对尾矿进行表面改性,能够改善尾矿表面亲疏水性、增加活性反应位点、提升颗粒分散性并增强与有机相的界面结合能力,同时再利用原位负载的方式,实现纳米氧化锌在尾矿表面的均匀负载,能够提升煤气化细渣尾矿的整体导热性能。为后续作为载体吸附有机相变材料提供更稳定的骨架与更快的储放热速率。所得到的K-CGFS-T@ZnO作为载体材料添加到有机相变材料中,能够提高相变复合材料的整体结构强度,并提升其导热性能。同时本发明提供的方法,工艺过程操作简单,成本较低,实现了煤气化细渣的高效综合利用。
Smart Images

Figure CN122898256A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of phase change materials technology, specifically relating to a modified coal gasification fine slag composite material, its preparation method and application, and a phase change composite material and its preparation method. Background Technology
[0002] Whether it's the utilization of renewable energy sources like solar power or the recovery of low-grade waste heat from industrial production, there's a significant bottleneck: a severe mismatch between heat supply and demand in time and space. Therefore, phase change energy storage technology, which utilizes the absorption or release of latent heat during phase change, has become a key solution for achieving spatiotemporal heat transfer, peak shaving, and improved overall energy utilization. Among numerous phase change energy storage materials, organic phase change materials (such as paraffin wax and fatty acids) are widely used in building energy conservation, solar thermal utilization, and other fields due to their significant advantages, including a wide phase change temperature range, no supercooling during condensation, good chemical stability, and low cost. Tetradecyl alcohol, as a typical organic phase change material, possesses advantages such as high latent heat of phase change (≥200 J / g), low supercooling, stable chemical properties, and non-toxicity and non-corrosiveness. However, tetradecanol still suffers from inherent defects of solid-liquid phase change materials: firstly, it is prone to flow and leakage during the solid-liquid phase change process, leading to a continuous decline in the material's heat storage capacity and a significant reduction in recycling efficiency; secondly, its intrinsic thermal conductivity is low, resulting in a slow heat storage and release response rate and significant thermal hysteresis, which severely restricts the operating efficiency and temperature control accuracy of the heat storage system, making it unable to directly meet the requirements of engineering applications. It needs to rely on carrier materials to achieve "shape stabilization" through physical adsorption and pore constraint. However, existing carriers (expanded graphite, graphene, aerogel, etc.) have problems such as high cost and complex preparation, making it difficult to meet the large-scale needs of large-scale energy storage projects.
[0003] On the other hand, with the rapid development of my country's modern coal chemical industry, coal gasification processes generate tens of millions of tons of solid waste annually—coal gasification slag. Coal gasification slag is a solid waste produced during the coal gasification process; large-scale accumulation of this waste can pollute soil, water, and air. Currently, its resource utilization rate is low, and it is mainly used in building materials, adsorbents, and other fields, but this involves high costs and low added value. Summary of the Invention
[0004] The purpose of this invention is to provide a modified coal gasification fine slag composite material, its preparation method and application, and a phase change composite material and its preparation method.
[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing modified coal gasification fine slag composite material, comprising the following steps: Modified coal gasification fine slag flotation tailings were obtained by modifying the tailings of coal gasification fine slag flotation using an aminosilane coupling agent. A dispersion containing modified coal gasification fine slag flotation tailings and a zinc salt solution are mixed. An inorganic alkali solution is added dropwise to the resulting mixture until the pH of the system is alkaline, and a liquid-phase reaction is carried out to obtain the modified coal gasification fine slag composite material.
[0006] Preferably, the modification process includes: The fine slag flotation tailings from coal gasification were mixed with ethanol and ultrasonically dispersed to obtain a dispersion. An aminosilane coupling agent was added to the dispersion, and the pH of the system was then adjusted to acidity for hydrolysis.
[0007] Preferably, the aminosilane-containing coupling agent includes KH550; The ultrasonic dispersion time is 20-60 min; The reagents used to adjust the pH of the system include at least one of glacial acetic acid or dilute hydrochloric acid. The mass of the aminosilane coupling agent is 1-3% of the mass of the coal gasification fine slag flotation tailings; The acidic pH value is 4-6; The hydrolysis is carried out under oil bath stirring conditions, wherein the oil bath stirring temperature is 60~80℃ and the stirring speed is 300~500rpm.
[0008] Preferably, the mass percentage of modified coal gasification fine slag flotation tailings in the dispersion is 4-6%; The zinc salt includes at least one of anhydrous zinc acetate and zinc acetate dihydrate; The zinc salt is 25-50% of the mass of the modified coal gasification fine slag flotation tailings; The alkaline pH value is 10-12; The temperature of the liquid phase reaction is 70~80℃; The dropping rate of the inorganic alkali solution is 0.5~0.7 mL / min, the liquid phase reaction time includes the dropping time of the inorganic alkali solution, and the total liquid phase reaction time is 1.5~2.5 h.
[0009] The present invention also provides a modified coal gasification fine slag composite material prepared by the preparation method described above, wherein the modified coal gasification fine slag composite material is modified coal gasification fine slag flotation tailings loaded with nano zinc oxide.
[0010] This invention also provides the application of the modified coal gasification fine slag composite material described in the above technical solution as a phase change carrier material.
[0011] The present invention also provides a phase change composite material, comprising the following components in parts by mass: 100 parts of organic phase change material and 30-50 parts of carrier material; The carrier material is the modified coal gasification fine slag composite material described in the above technical solution.
[0012] Preferably, the organic phase change material includes at least one of tetradecyl alcohol, phase change paraffin, and polyethylene glycol.
[0013] The present invention also provides a method for preparing the phase change composite material described in the above technical solution, comprising the following steps: The dispersion containing the carrier material is added to the molten organic phase change material for mixing to obtain the phase change composite material.
[0014] Preferably, the mixing is carried out under stirring conditions, wherein the stirring temperature is 70~80℃, the stirring speed is 300~500rpm, and the stirring time is 1~2h.
[0015] In this invention, the surface modification of tailings using an aminosilane coupling agent improves the hydrophilicity / hydrophobicity of the tailings surface, increases active reaction sites, enhances particle dispersibility, and strengthens the interfacial bonding with the organic phase. Simultaneously, in-situ loading achieves uniform loading of nano-zinc oxide on the tailings surface, improving the overall thermal conductivity of the coal gasification fine tailings. This provides a more stable framework and faster heat storage / release rate for subsequent adsorption of organic phase change materials. The resulting K-CGFS-T@ZnO, added as a carrier material to organic phase change materials, improves the overall structural strength of the phase change composite material and enhances its thermal conductivity. Furthermore, the method provided by this invention is simple to operate, low in cost, and achieves efficient and comprehensive utilization of coal gasification fine tailings.
[0016] This invention provides a phase change carrier material based on coal gasification fine slag. The coal gasification fine slag is used as the shaping carrier for the phase change material. At the same time, the carrier is subjected to directional modification treatment. The microporous structure of the carrier adsorbs molten organic phase change material, thereby improving the thermal conductivity and photothermal conversion efficiency of the phase change composite material. Ultimately, this invention achieves the dual goals of high-value utilization of coal gasification fine slag and low-cost preparation of phase change energy storage materials. Attached Figure Description
[0017] Figure 1 A schematic diagram of the process for preparing the phase change composite material provided by the present invention; Figure 2 This is a SEM image of the coal gasification fine slag flotation tailings obtained in Example 3; Figure 3 This is a SEM image of the residual carbon area in the coal gasification fine slag flotation tailings obtained in Example 3; Figure 4 The image shows a SEM image of the modified coal gasification fine slag composite material obtained in Example 3. Figure 5This is a mapping diagram of the modified coal gasification fine slag composite material obtained in Example 3. Detailed Implementation
[0018] This invention provides a method for preparing modified coal gasification fine slag composite material, comprising the following steps: Modified coal gasification fine slag flotation tailings (CGFS-T) was obtained by modifying it with an aminosilane coupling agent. A dispersion containing modified coal gasification fine slag flotation tailings and a zinc salt solution were mixed. An inorganic alkali solution was added dropwise to the resulting mixture until the pH of the system was alkaline, and a liquid-phase reaction was carried out to obtain the modified coal gasification fine slag composite material (K-CGFS-T@ZnO).
[0019] This invention utilizes an aminosilane coupling agent to modify coal gasification fine slag flotation tailings (CGFS-T) to obtain modified coal gasification fine slag flotation tailings (K-CGFS-T).
[0020] In this invention, the preferred method for preparing the coal gasification fine slag flotation tailings (CGFS-T) includes: The fine slag from coal gasification is mixed with water to obtain a slurry; The slurry, collector and frother are mixed, and the resulting system is aerated for flotation. After bubbles appear, the bubbles are scraped off, and the concentrate and tailings are collected separately. The tailings are coal gasification fine slag flotation tailings (CGFS-T).
[0021] This invention mixes coal gasification slag with water to obtain a slurry.
[0022] The present invention does not have any special limitation on the source of the coal gasification fine slag; any source well known to those skilled in the art can be used. In a specific embodiment of the present invention, the coal gasification fine slag is preferably from Huainan Zhong'an United Coal Chemical Co., Ltd.
[0023] In this invention, the coal gasification slag preferably comprises the following components in weight percentage (by XRF testing): 50-60% silica, 20-22% alumina, 6-9% calcium oxide, and 4-7% iron oxide. In this invention, the carbon content of the coal gasification slag is preferably 14-20 wt% (by loss on ignition determination).
[0024] In this invention, before mixing with water, it is preferable to further include ball milling the coal gasification fine slag. The ball-to-material ratio of the ball milling is preferably 9~12:1, specifically 9:1, 10:1, 11:1, or 12:1; the rotation speed is preferably 200~400 rpm, specifically 200 rpm, 300 rpm, or 400 rpm; the time is preferably 2~4 hours, specifically 2 hours, 3 hours, or 4 hours; the ball milling is preferably performed using an XM-4 planetary ball mill; and the particle size of the coal gasification fine slag obtained after ball milling is preferably 10~20 μm.
[0025] In this invention, the mixing is preferably carried out under stirring conditions, and the stirring time is preferably 2-4 minutes, specifically 2 minutes, 3 minutes, or 4 minutes. In this invention, the solid content of the slurry is preferably 80-100 g / L, specifically 80 g / L, 90 g / L, or 100 g / L.
[0026] After obtaining the slurry, the present invention mixes the slurry, collector and frother, and aerates the resulting system for flotation. After bubbles appear, the bubbles are scraped off, and the concentrate and tailings are collected separately.
[0027] In this invention, the collector preferably comprises kerosene and diesel oil, and the mass ratio of kerosene to diesel oil is preferably (0.8~1.2):1, specifically 0.8:1, 0.9:1, 1.0:1, 1.1:1, or 1.2:1; the frother preferably comprises pine oil; the mass of the collector is preferably 1.0~1.4% of the mass of the coal gasification fine slag, specifically 1.0%, 1.1%, 1.2%, 1.3%, or 1.4%; the mass of the frother is preferably 0.6~1.2% of the mass of the coal gasification fine slag, specifically 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, or 1.2%. In this invention, the mixing process is preferably as follows: under stirring conditions, the collector and the frother are added to the slurry in sequence; the stirring time after adding the collector is preferably 2 to 5 minutes, specifically 2 minutes, 3 minutes, 4 minutes, or 5 minutes; the stirring time after adding the frother is preferably 10 to 16 seconds, specifically 10 seconds, 11 seconds, 12 seconds, 13 seconds, 14 seconds, 15 seconds, or 16 seconds.
[0028] In this invention, the flotation is preferably carried out under stirring conditions, and the stirring speed is preferably 1400~2200 rpm, specifically 1400 rpm, 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm, 2100 rpm, or 2200 rpm; the aeration rate is preferably 0.20~0.30 L / (m³). 2•min). This invention does not impose any particular limitation on the process of skimming bubbles; any method well-known to those skilled in the art can be used. In this invention, the skimming time is preferably 1-2 minutes. In this invention, after skimming bubbles, it is also preferable to wash and dry the skimmed material to obtain a concentrate with a high carbon content; and to dry and dehydrate the remaining system after skimming bubbles to obtain tailings with a high inorganic mineral content (i.e., coal gasification fine slag flotation tailings). In this invention, the flotation is preferably carried out using a 1.5L single-cell flotation machine (RK / FD).
[0029] In this invention, the modification process preferably includes: mixing coal gasification fine slag flotation tailings with ethanol and ultrasonically dispersing to obtain a dispersion; An aminosilane coupling agent was added to the dispersion, and the pH of the system was then adjusted to acidity for hydrolysis.
[0030] In this invention, the preferred ratio of the coal gasification fine slag flotation tailings to ethanol is 2-4 g; 50-100 mL; the preferred ultrasonic dispersion time is 20-60 min, specifically 20 min, 30 min, 40 min, 50 min, or 60 min. In this invention, prior to mixing, the coal gasification fine slag flotation tailings are preferably subjected to ball milling; the preferred ball-to-material ratio for ball milling is 9-12:1, specifically 9:1, 10:1, 11:1, or 12:1; the preferred rotation speed is 200-400 rpm, specifically 200 rpm, 300 rpm, or 400 rpm; and the preferred time is 2-4 h, specifically 2 h, 3 h, or 4 h.
[0031] In this invention, the aminosilane coupling agent preferably includes KH550; the mass of the aminosilane coupling agent is preferably 1-3% of the mass of the coal gasification fine slag flotation tailings, specifically 1%, 2%, or 3%; the reagent used to adjust the pH value of the system preferably includes at least one of glacial acetic acid or dilute hydrochloric acid; this invention does not have specific limitations on the concentration and amount of the reagent, as long as the desired pH value is obtained. In this invention, the acidic pH value is preferably 4-6, specifically 4, 5, or 6. In this invention, the hydrolysis is preferably carried out under oil bath stirring conditions, the oil bath stirring temperature is preferably 60-80℃, specifically 60℃, 70℃, or 80℃; the stirring speed is preferably 300-500 rpm, specifically 300 rpm, 400 rpm, or 500 rpm; and the time is preferably 20-40 min, specifically 20 min, 30 min, or 40 min.
[0032] In this invention, the modified coal gasification fine slag flotation tailings obtained are preferably in the form of a suspension, which is used as a dispersion containing the modified coal gasification fine slag flotation tailings in the next step.
[0033] After obtaining the modified coal gasification fine slag flotation tailings (K-CGFS-T), the present invention mixes the dispersion containing the modified coal gasification fine slag flotation tailings with a zinc salt solution, adds an inorganic alkali solution dropwise to the resulting mixture until the pH of the system is alkaline, and performs a liquid-phase reaction to obtain the modified coal gasification fine slag composite material (K-CGFS-T@ZnO).
[0034] In this invention, the mass percentage of modified coal gasification fine slag flotation tailings in the dispersion is preferably 4-6%, and more preferably 5%.
[0035] In this invention, the zinc salt preferably includes at least one of anhydrous zinc acetate and zinc acetate dihydrate; the mass of the zinc salt is preferably 25-50% of the mass of the modified coal gasification fine slag flotation tailings, specifically 25%, 30%, 35%, 37.5%, 40%, 45%, or 50%. In this invention, the solvent in the zinc salt solution preferably includes deionized water and anhydrous ethanol, and the volume ratio of deionized water to anhydrous ethanol is preferably (3-5):1, specifically 3:1, 4:1, or 5:1; the preparation method of the zinc salt solution preferably includes: dissolving the zinc salt in the solvent and then performing ultrasonication; the ultrasonication time is preferably 20-40 min, specifically 20 min, 30 min, or 40 min.
[0036] In this invention, the mixing process preferably includes: preheating the zinc salt solution and then adding the dispersion containing modified coal gasification fine slag flotation tailings; the preheating temperature is preferably 60~80℃, specifically 60℃, 70℃, or 80℃; the time is preferably 20~40min, specifically 20min, 30min, or 40min; the preheating is preferably carried out under stirring conditions.
[0037] In this invention, the inorganic alkaline solution preferably comprises a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is preferably 0.5~1 mol / L, specifically 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, or 1 mol / L. During the dropwise addition, the mixing system is preferably under stirring. The dropping rate of the inorganic alkaline solution is preferably 0.5~0.7 mL / min, specifically 0.5 mL / min, 0.6 mL / min, or 0.7 mL / min. In this invention, the alkaline pH value is preferably 10~12, specifically 10, 11, or 12.
[0038] In this invention, the preferred temperature for the liquid-phase reaction is 70-80°C; the preferred reaction time includes the time for adding the inorganic alkali solution, and the preferred total reaction time is 1.5-2.5 h, specifically 1.5 h, 2.0 h, or 2.5 h; the liquid-phase reaction is preferably carried out under stirring conditions. After the liquid-phase reaction, this invention further preferably includes allowing the reaction system to stand, washing the obtained product with water, and drying it; the preferred standing time is 24 h; the preferred water washing is deionized water, and the preferred number of water washings is 4 times; the preferred drying temperature is 70°C.
[0039] In this invention, a schematic diagram of the preparation process of the modified coal gasification fine slag composite material (K-CGFS-T@ZnO) is shown below. Figure 1 As shown.
[0040] The present invention also provides a modified coal gasification fine slag composite material prepared by the preparation method described above, wherein the modified coal gasification fine slag composite material is nano-zinc oxide-supported modified coal gasification fine slag flotation tailings.
[0041] This invention also provides the application of the modified coal gasification fine slag composite material described in the above technical solution as a phase change carrier material.
[0042] The present invention also provides a phase change composite material, comprising the following components in parts by mass: 100 parts of organic phase change material and 30-50 parts of carrier material; The carrier material is the modified coal gasification fine slag composite material described in the above technical solution.
[0043] In this invention, the organic phase change material preferably includes at least one of tetradecyl alcohol, phase change paraffin, and polyethylene glycol.
[0044] In this invention, the mass fraction of the carrier material can be 30 parts, 40 parts, or 50 parts.
[0045] The present invention also provides a method for preparing the phase change composite material described in the above technical solution, comprising the following steps: The dispersion containing the carrier material is added to the molten organic phase change material for mixing to obtain the phase change composite material.
[0046] In this invention, the preparation of the dispersion containing the carrier material preferably includes: ultrasonically dispersing the carrier material in ethanol; the preferred ratio of the carrier material to ethanol is 2-4 g: 50-100 mL, specifically 3 g: 80 mL; the preferred ultrasonic dispersion time is 30-50 min, specifically 30 min, 40 min, or 50 min. In this invention, the mixing is preferably carried out under stirring conditions; the preferred stirring temperature is 70-80°C, specifically 70°C, 75°C, or 80°C; the preferred stirring speed is 300-500 rpm, specifically 300 rpm, 400 rpm, or 500 rpm; and the preferred stirring time is 60-120 min, specifically 60 min, 90 min, or 120 min.
[0047] In this invention, after mixing, the process preferably further includes placing the resulting system in a mold and sequentially drying and room temperature molding; the drying temperature is preferably 70°C, and the drying time is preferably 12 hours. This invention does not impose any special limitations on the room temperature molding process; any process well-known to those skilled in the art can be used.
[0048] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0049] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0050] Example 1 The coal gasification slag used was from Huainan Zhong'an United Coal Chemical Co., Ltd. The composition of the slag was as follows, as determined by XRF testing: 54.79 wt% silica, 21.07 wt% alumina, 8.21 wt% calcium oxide, and 5.46 wt% iron oxide; the carbon content was 16.11 wt% as determined by loss on ignition.
[0051] The fine coal gasification slag was put into a ball mill for ball milling. The ball-to-material ratio was 12:1, the rotation speed was 350 rpm, and the ball milling time was 2 hours to obtain the fine coal gasification slag with a particle size of 10~20μm. Weigh 90g of ball-milled coal gasification fine slag and place it in a flotation cell. Add water to the 1.5L mark, turn on the stirring button, and stir for 3 minutes to obtain a slurry. Inject a compound collector—kerosene and diesel oil (kerosene to diesel oil mass ratio of 1:1)—into the slurry using a micro-syringe. Stir for 3 minutes, then inject a frother—2-octanol—into the slurry using a micro-syringe. The amount of collector and frother is 1.2% of the mass of the coal gasification fine slag. Stir for 12 seconds, then open the gas valve and start aeration under stirring (speed of 1800 rpm) (aeration rate of 0.25L / (m³)). 2 After bubbles appear, scrape them off with a scraper for 3 minutes. After scraping, wash and dry the scraped material to obtain a concentrate with a high carbon content. Dry and dehydrate the remaining system after scraping to obtain coal gasification fine slag flotation tailings (CGFS-T) with a high inorganic mineral content. CGFS-T was ball-milled at a ball-to-material ratio of 12:1 at 350 rpm for 2 hours. The ball-milled CGFS-T was then added to 100 mL of ethanol and ultrasonically dispersed for 40 minutes. A silane coupling agent (specifically KH550, at 2% of the mass of the coal gasification fine slag flotation tailings) was then added, and glacial acetic acid was added to adjust the pH to 5. The mixture was stirred at 400 rpm for 30 minutes at 70°C to obtain a modified coal gasification fine slag flotation tailings (K-CGFS-T) suspension (where the modified coal gasification fine slag flotation tailings comprised 5% by mass). Next, take anhydrous zinc acetate, the mass of which is 25% of the modified coal gasification fine slag flotation tailings, and disperse it in 150 mL of a mixed solvent of deionized water and ethanol (volume ratio of deionized water to ethanol 3:1), and sonicate for 40 min. Zinc acetate solution was preheated in an oil bath at 70℃ for 40 min with stirring, then K-CGFS-T suspension was added, followed by dropwise addition of 1 mol / L sodium hydroxide solution at a rate of 0.6 mL / min. The addition was stopped when the pH of the system reached 12. The total liquid-phase reaction time was 2 h at 70℃ (including the time for adding sodium hydroxide solution). After standing for 24 h, the obtained product was washed three times with deionized water and dried in a 70℃ oven to constant weight to obtain the modified coal gasification fine slag composite material K-CGFS-T@ZnO, which can be used as a phase change carrier material. Preparation of phase change composite material: Take 100 parts of phase change material tetradecyl alcohol and heat it to a molten state; then take 40 parts of phase change carrier material K-CGFS-T@ZnO, add ethanol (the ratio of carrier material to ethanol is 3g:80mL), and disperse it with ultrasonic assistance for 40min. Then add the dispersion to the molten tetradecyl alcohol and stir in an oil bath at 75℃ and 400rpm for 90min. Then place it in a mold, put it in an oven to evaporate the ethanol, and after drying, shape it at room temperature.
[0052] Example 2 K-CGFS-T@ZnO phase change carrier material was obtained and phase change composite material was prepared according to Example 1, the difference being that the mass of anhydrous zinc acetate was 37.5% of the mass of K-CGFS-T.
[0053] Example 3 K-CGFS-T@ZnO phase change carrier material was obtained and phase change composite material was prepared according to Example 1, except that the mass of anhydrous zinc acetate was 50% of the mass of K-CGFS-T.
[0054] Example 4 K-CGFS-T@ZnO phase change carrier material was obtained and phase change composite material was prepared according to Example 3, except that the number of parts of K-CGFS-T@ZnO was 30 parts.
[0055] Example 5 K-CGFS-T@ZnO phase change carrier material was obtained and phase change composite material was prepared according to Example 3, except that the number of parts of K-CGFS-T@ZnO phase change carrier material was 50 parts.
[0056] Comparative Example 1 Pure tetradecyl alcohol phase change material.
[0057] Comparative Example 2 CGFS-T was obtained and a phase change composite material was prepared according to Example 1, except that no silane coupling agent modification was performed and the amount of anhydrous zinc acetate added was 0%.
[0058] Comparative Example 3 K-CGFS-T@ZnO phase change carrier material was obtained and phase change composite material was prepared according to the method of Example 1, the difference being that the silane coupling agent was KH560.
[0059] Comparative Example 4 K-CGFS-T@ZnO phase change carrier material was obtained and phase change composite material was prepared according to the method of Example 1, the difference being that the silane coupling agent was KH570.
[0060] Performance testing The phase transition enthalpy values of the phase change composite materials in Examples 1-5 and Comparative Examples 1-4 during the melting and solidification processes were tested using a differential scanning calorimeter. The test conditions were as follows: under a nitrogen atmosphere, the temperature range was 0℃~70℃, the heating rate was 5℃ / min, and the sample weight was approximately 8mg. The thermal conductivity of the phase change composite materials in Examples 1-5 and Comparative Examples 1-4 was tested using a thermal conductivity meter (Hotdisk), and the test results are shown in Table 1. Table 1. Performance test results of phase change composite materials obtained in the examples and comparative examples.
[0061] The main components of coal gasification fine slag are residual char, spherical SiO2, and Al2O3. The residual char has a porous structure, providing a large specific surface area. Silane coupling agents further improve its surface chemical activity, providing more contact sites for loading on nano-zinc oxide and enhancing interfacial bonding. Simultaneously, its porous structure can adsorb molten phase change materials, reducing leakage. Generally, the presence of inorganic components such as SiO2 and Al2O3 can improve the thermal conductivity of the material. Through flotation treatment of coal gasification fine slag, inorganic minerals such as spherical SiO2 are enriched, forming a continuous thermally conductive network, which improves the thermal conductivity of the phase change composite material and further enhances its overall thermal conductivity.
[0062] Figure 2 This is a SEM image of the coal gasification fine slag flotation tailings obtained in Example 3; Figure 3 This is a SEM image of the residual carbon area in the coal gasification fine slag flotation tailings obtained in Example 3; Figure 4 The image shows a SEM image of the modified coal gasification fine slag composite material obtained in Example 3. Figure 5 This is a mapping diagram of the modified coal gasification fine slag composite material obtained in Example 3.
[0063] pass Figure 2 , Figure 3 It can be seen that the modified tailings contain a large number of inorganic mineral glass microspheres and porous, irregular blocky regions. This structure originates from the non-equilibrium solidification process of high-temperature melting and quenching during coal gasification—the inorganic mineral components melt into a liquid phase in the high-temperature zone of the gasifier, and then rapidly shrink and solidify into spherical particles after water quenching. The unreacted residual carbon acts as the substrate for the molten mineral droplets during this process, and the two are "frozen" into interlocking micro-units during the quenching instant. The residual carbon skeleton is irregularly sponge-like, and its interior and surface are occupied by glass microspheres ranging from several micrometers to tens of micrometers in size, presenting an overall rough morphology with undulating surfaces, providing more contact sites. At the same time, this non-smooth surface is conducive to the subsequent flow and loading of molten PCM. Figure 4 It can be seen that the surface of the glass microspheres and the irregular porous blocky regions are loaded with a large number of nano-zinc oxide particles; from Figure 5 The results show that the modified tailings contain a relatively high amount of Zn, indicating that nano-zinc oxide was successfully loaded into the tailings.
[0064] In summary, the inorganic components in the coal gasification tailings can effectively improve the thermal conductivity of the phase change composite material. After flotation treatment, the inorganic components in the tailings are further enriched, and continuous spherical SiO2 forms a dense thermally conductive network, accelerating the heat diffusion rate and promoting the absorption, release, and transfer of heat in the system. Simultaneously, silane coupling agent modification improves the surface properties of the carrier, providing sufficient active binding sites for the loading of nano-zinc oxide. The unique surface and size effects of nano-zinc oxide further improve the thermal conductivity pathway of the composite system, significantly enhancing its thermal conductivity. When the amount of anhydrous zinc acetate added is 50%, the thermal conductivity is highest, with the enthalpy of melting remaining above 150 J / g and the enthalpy of solidification remaining above 100 J / g. This indicates that the modified tailings and the introduction of nano-zinc oxide can improve the thermal conductivity of the material while maintaining good thermal energy storage capacity. With a fixed zinc acetate content of 50%, increasing the amount of K-CGFS-T@ZnO will decrease the melting enthalpy and solidification enthalpy, which is due to the decrease in the phase change material tetradecyl alcohol. At the same time, the overall thermal conductivity of the composite material increases, demonstrating the enhancing effect of K-CGFS-T@ZnO on thermal conductivity.
[0065] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a modified coal gasification fine slag composite material, characterized in that, Includes the following steps: Modified coal gasification fine slag flotation tailings were obtained by modifying the tailings of coal gasification fine slag flotation using an aminosilane coupling agent. A dispersion containing modified coal gasification fine slag flotation tailings and a zinc salt solution are mixed. An inorganic alkali solution is added dropwise to the resulting mixture until the pH of the system is alkaline, and a liquid-phase reaction is carried out to obtain the modified coal gasification fine slag composite material.
2. The preparation method according to claim 1, characterized in that, The modification process includes: The fine slag flotation tailings from coal gasification were mixed with ethanol and ultrasonically dispersed to obtain a dispersion. An aminosilane coupling agent was added to the dispersion, and the pH of the system was then adjusted to acidity for hydrolysis.
3. The preparation method according to claim 2, characterized in that, The aminosilane coupling agent includes KH550; The ultrasonic dispersion time is 20-60 min; The reagents used to adjust the pH of the system include at least one of glacial acetic acid or dilute hydrochloric acid. The mass of the aminosilane coupling agent is 1-3% of the mass of the coal gasification fine slag flotation tailings; The acidic pH value is 4-6; The hydrolysis is carried out under oil bath stirring conditions, wherein the oil bath stirring temperature is 60~80℃ and the stirring speed is 300~500rpm.
4. The preparation method according to claim 1, characterized in that, The mass percentage of modified coal gasification fine slag flotation tailings in the dispersion is 4-6%; The zinc salt includes at least one of anhydrous zinc acetate and zinc acetate dihydrate; The zinc salt is 25-50% of the mass of the modified coal gasification fine slag flotation tailings; The alkaline pH value is 10-12; The temperature of the liquid phase reaction is 70~80℃; The dropping rate of the inorganic alkali solution is 0.5~0.7 mL / min, the liquid phase reaction time includes the dropping time of the inorganic alkali solution, and the total liquid phase reaction time is 1.5~2.5 h.
5. The modified coal gasification fine slag composite material prepared by the preparation method according to any one of claims 1 to 4, characterized in that, The modified coal gasification fine slag composite material is modified coal gasification fine slag flotation tailings loaded with nano zinc oxide.
6. The application of the modified coal gasification fine slag composite material as described in claim 5 as a phase change carrier material.
7. A phase change composite material, characterized in that, Based on parts by weight, it includes the following components: 100 parts of organic phase change material and 30-50 parts of carrier material; The carrier material is the modified coal gasification fine slag composite material as described in claim 5.
8. The phase change composite material according to claim 7, characterized in that, The organic phase change material includes at least one of tetradecyl alcohol, phase change paraffin, and polyethylene glycol.
9. The method for preparing the phase change composite material according to claim 7 or 8, characterized in that, Includes the following steps: The dispersion containing the carrier material is added to the molten organic phase change material for mixing to obtain the phase change composite material.
10. The preparation method according to claim 9, characterized in that, The mixing is carried out under stirring conditions, with the stirring temperature being 70~80℃, the stirring speed being 300~500rpm, and the time being 1~2h.